Chronic clenbuterol treatment compromises force production without directly altering skeletal muscle contractile machinery. (27th February 2015) - Py, G.; Ramonatxo, C.; Sirvent, P.; Sanchez, A. M. J.; Philippe, A. G.; Douillard, A.; Galbès, O.; Lionne, C.; Bonnieu, A.; Chopard, A.; Cazorla, O.; Lacampagne, A.; et al.
Abstract : Key points: Clenbuterol is an adrenergic receptor agonist known to induce skeletal muscle hypertrophy and a shift towards faster muscle fibres, when administered chronically at high doses. However, when normalized to the muscle surface area, the increase in muscle force is no longer increased and even depressed. We show that muscle contraction and relaxation force kinetics were significantly reduced particularly in fast contracting muscles. We show that action potential‐elicited Ca 2+ transients were depressed in the fast contracting muscle. Our data show that chronic clenbuterol treatment reduces contractile efficiency, with altered contraction and relaxation kinetics, but without directly altering the contractile machinery. Lower Ca 2+ release during contraction could partially explain these deleterious effects. Abstract: Clenbuterol is a β2 ‐adrenergic receptor agonist known to induce skeletal muscle hypertrophy and a slow‐to‐fast phenotypic shift. The aim of the present study was to test the effects of chronic clenbuterol treatment on contractile efficiency and explore the underlying mechanisms, i.e. the muscle contractile machinery and calcium‐handling ability. Forty‐three 6‐week‐old male Wistar rats were randomly allocated to one of six groups that were treated with either subcutaneous equimolar doses of clenbuterol (4 mg kg −1  day −1 ) or saline solution for 9, 14 or 21 days. In addition to the muscle hypertrophy, although an 89% increase in absolute maximal tetanic force ( P o ) was noted, specific maximal tetanic force (sPo) was unchanged or even depressed in the slow twitch muscle of the clenbuterol‐treated rats ( P  < 0.05). The fit of muscle contraction and relaxation force kinetics indicated that clenbuterol treatment significantly reduced the rate constant of force development and the slow and fast rate constants of relaxation in extensor digitorum longus muscle ( P  < 0.05), and only the fast rate constant of relaxation in soleus muscle ( P  < 0.05). Myofibrillar ATPase activity increased in both relaxed and activated conditions in soleus ( P  < 0.001), suggesting that the depressed specific tension was not due to the myosin head alteration itself. Moreover, action potential‐elicited Ca 2+ transients in flexor digitorum brevis fibres (fast twitch fibres) from clenbuterol‐treated animals demonstrated decreased amplitude after 14 days (−19%, P  < 0.01) and 21 days (−25%, P  < 0.01). In conclusion, we showed that chronic clenbuterol treatment reduces contractile efficiency, with altered contraction and relaxation kinetics, but without directly altering the contractile machinery. Lower Ca 2+ release during contraction could partially explain these deleterious effects.